Navigating research funding with confidence - Spencely, Carol; Acuña-Rivera, Marcela; Denicolo, Pam (London : SAGE Publications Ltd, 2020)
A timely manual in the current climate of increasingly underfunded departments and institutions, this book offers insight into how to secure, manage and effectively research funding in the changing order of global economy and competing research priorities. It gives you the perspectives of those who seek, and those who award research funding, such as governments, companies and foundations. Examining the full cycle and elements of influence of research funding, this book comes with: • Practical case studies, • Lists of potential funding sources that you can use to enhance your funding generation efforts, and • Explanatory videos Clear and digestible, this text delivers systematic guidance for early career researchers and students in Graduate Schools, Doctoral Colleges, Research Methods Programmes, Academic and Research Staff Development Programmes.
Includes index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Research -- Finance; Research grants